2021
DOI: 10.1155/2021/5574512
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Root Canal Anatomy of Maxillary and Mandibular Permanent Canines in Saudi Subpopulation: A Cone-Beam Computed Tomography (CBCT) Study

Abstract: The objective of this investigation was to evaluate the root canal anatomy of permanent canines in a Saudi subpopulation utilizing CBCT. A total of 1328 CBCT images of maxillary (634) and mandibular (694) permanent canines were collected from Saudi patients who visited the College of Dentistry at King Saud University in Riyadh. The images were analyzed for root and canal numbers, canal configuration types, and symmetry between the bilateral canine teeth in each arch. Gender, age, and tooth position were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 40 publications
6
32
0
Order By: Relevance
“…No studies investigated anterior teeth, except for two studies that evaluated maxillary canines [ 17 , 22 ], which showed that the anterior teeth had one root (100%), 98.4% had one canal, and 1.6% had two canals. Vertucci type I was the most predominant canal configuration (98.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies investigated anterior teeth, except for two studies that evaluated maxillary canines [ 17 , 22 ], which showed that the anterior teeth had one root (100%), 98.4% had one canal, and 1.6% had two canals. Vertucci type I was the most predominant canal configuration (98.3%).…”
Section: Discussionmentioning
confidence: 99%
“…From 2006 to the present, several studies have utilized different methodologies to analyze maxillary permanent dentition anatomy in various populations in the Kingdom of Saudi Arabia (KSA) [11,13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. In some of these studies, the sample was defined as "Saudi population," whereas in others the sample was described as "Saudi subpopulation" and was from different regions of Saudi Arabia, most of which were from the central region.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] In the present systemic review, the ten studies included better comparable imaging for the root canals in the permanent teeth using the CBCT than the conventional techniques. [ 2 3 4 9 11 12 13 14 15 16 ] In three of the studies, there were disagreements with the root canal assessment of the maxillary teeth isthmus and the total area. [ 5 6 8 ] None of the studies included were described the incidence of the radis molaris, or any other variations of the normal anatomy to keep out the bias.…”
Section: Discussionmentioning
confidence: 99%
“…The CBCT images were interpreted at the Radiology Department of the Dental College at King Saud University by one endodontist and three trained interns for the number of roots and canals and types of canal configuration. Consultations were undertaken with an oral radiologist [ 26 ]. For image assessment, Planmeca Romexis Viewer software was utilized (Planmeca, Roselle IL).…”
Section: Methodsmentioning
confidence: 99%
“…A professional technician acquired the radiological images according to the manufacturer's recommendation using Planmeca ProMax 3D (PLANMECA, Roselle, IL, USA) and a CS9300 3D digital imaging system (Carestream, Rochester, NY). The voxel size was 75–600 μ m, with small or large field of view (FOVs), the slice thickness was 0.2 mm viewed from the coronal to apical region, and the exposure time was 3–15 seconds [ 26 ].…”
Section: Methodsmentioning
confidence: 99%